Assessing the Risk of Oil Spills in the Mediterranean: the Case of the Route from the Black Sea to Italy - Andrea Bigano; Paul Sheehan (Fondazione Eni Enrico Mattei (FEEM), 2006)
Recent major spills on European coasts have highlighted the primary policy relevance for the EU of oil spills. This paper assesses the risks related to carrying oil to the EU along the route from the Russian Black Sea coast to Sicily, Italy (one of the most congested and strategically relevant European import routes). We develop a methodology based on Fault Tree Analysis, and we apply it to the most likely causes of an oil spill. We couple the resulting probabilities with data on expected spill size, types of oil carried and cleanup costs, to estimate expected costs for cleanup and loss of cargo. The route analysed appears to be a risky one; there is a high to very high risk of a spill along this route. The Turkish Straits turn out to be the major danger point; however, there is no obvious hierarchy amongst the other sites along the route.
Keywords: Q32; Q51; Q52; Q53; 330; Oil spills; Cleanup costs; Risk analysis; Meeresverschmutzung; Umweltkosten; Mittelmeerraum